Estudo do Modelo de Ginzburg-Landau e as Cerâmicas Supercondutoras - Alves Junior, Leonidio Joaquim (2008)
In this dissertation we have worked out a study of thermodynamics described by the model of Ginzburg–Landau. We emphasized the points that always appear in the literature of superconducting temperature until 30 K. We analyzed the phase transitions that occur in the samples described by this model. It was also made a brief introduction to the properties of superconducting ceramics, taking the example of cuprates based on mercury (Hg - 1223). We noted that by spraying of the superconducting chip, appeared two different critical temperatures. We concluded the dissertation proposing an extension of the model Ginzburg - Landau describing this splitting of the critical temperature.